The effect of light intensity of blinking LED toward coral fishes catch of trap in the waters of Ternate Island - Ammari, Janhar Al (Universitas Sam Ratulangi, 2013)
Using blinking Light Emiting Diode (LED) could increase the fishing power of bottom traps. The objective of this research was to study the effect of light intensity of LED (blinking lamp) inside the trap and moon phase toward the capture of coral fishes. Three light intensities of LED were used: 35 lux (2 LED), 70 lux (4 LED), 105 lux (6 LED) and one without blinking lamp as a control. Catch data were collected using 12 units of bottom traps operating in coral waters of Ternate Island at depths around 5 to 7 m.Data analysis wasdone based on randomized block design. The catch was 181 fish in total comprising 12 families, 17 genera and 28 species. Analysis of variance showed that using different light intensity of LED on bottom traps and different moon phase caused highly significant effect in catch. Least significant differences test showed that using light intensity 105 lux (6 LED) inside the trap is not significant in catch to 70 lux (4 LED), but highly significant to 35 lux (2 LED) and control. Light intensity 70 lux (4 LED) is not significant in catch to 35 lux (2 LED), but highly significant to control. There was no significant difference between light intensity 70 lux (4 LED) and control. Catch of trap could increase when using higher light intensity of blinking lamp (LED) and the catch of trap also increase when operated around dark moon. It is better to use high light intensity of blinking lamp (105 lux) inside the trap, and operated in dark moon to catch coral fishes© Penggunaan lampu LED (Ligh Emiting Diode) berkedip didalam bubu diduga dapat meningkatkan kemampuan tangkap. Penelitian ini bertujuan untuk mempelajari pengaruh intensitas cahaya lampu LED berkedip di dalam bubu dan fase umur bulan terhadap hasil tangkapan ikan-ikan karang. Tiga jenis intensitas cahaya lampu yang digunakan, yaitu 35 lux (2 LED), 70 lux (4 LED), 105 lux (6 LED), dan lampu LED tanpa berkedip sebagai kontrol. Data dikumpulkan dengan mengoperasikan 12 unit bubu di perairan karang Pulau Ternate pada kedalaman sekitar 5–7 m; dan dianalisis berdasarkan Rancangan Acak Kelompok. Hasil tangkapan total sebanyak 181 ekor; terdiri dari 15 famili, 25 genus, dan 35 jenis. Analisis sidik ragam menunjukkan bahwa perbedaan intensitas cahaya lampu LED dalam bubu dan perbedaan fase umur bulan berpengaruh sangat nyata terhadap hasil tangkapan. Hasil uji BNT untuk perlakuan menunjukkan bahwa penggunaan lampu 6 LED (105 lux) pada bubu tidak berbeda nyata dengan penggunaan lampu 4 LED (70 lux) tetapi berbeda sangat nyata dengan penggunaan lampu 2 LED (35 lux) dan Kontrol. Demikian juga lampu 4 LED tidak berbeda nyata dengan lampu 2 LED tetapi berbeda sangat nyata dengan Kontrol; sedangkan antara lampu 2 LED dan Kontrol tidak ada perbedaan yang nyata. Hasil tangkapan bubu meningkat ketika menggunakan lampu kedip dengan intensitas yang lebih tinggi; dan dioperasikan pada saat bulan gelap. Sebaiknya menggunakan lampu LED berkedip 105 lux dan dioperasikan saat bulan gelap untuk menangkap ikan-ikan karang dengan bubu©